Terapia com florais de Bach - MONTEIRO, Ana Luiza da Silva; CALDEIRA, Débora Cristina Baldo; SILVA, Caroline Tavares da; CALDEIRA, Micael Aparecida Scarabelli (059, 2023)
A Terapia Floral de Bach foi criada por Edward Bach em 1886 na Inglaterra com a proposta de oferecer tratamento a sintomas emocionais com o uso de 38 Florais, sendo indicado para uso em qualquer período da vida com segurança. Nas crianças observa-se uma resposta praticamente imediata com o uso dos florais e desta forma a Terapia Floral de Bach encontra aplicação crescente na pediatria, faixa etária onde encontramos frequentes quadros clínicos associados aos medos e dificuldade de adaptação. No Brasil esta prática foi agregada na Política Nacional de Práticas Integrativas e Complementares ao SUS em março de 2018. Diversos trabalhos foram realizados em vários países sobre o uso de florais na infância e adolescência para tratamento de medos e traumas, do Transtorno do Déficit de Atenção e Hiperatividade, da enurese noturna secundária e do vitiligo, com resultados positivos quanto à sua eficácia quando comparado ao grupo controle.

Bach Flower Therapy was created by Edward Bach in 1886 in England with the proposalto offer treatment to emotional symptoms with the use of 38 Flower Remedies, being indicatedfor use in any period of life safely. In children, there is aa practically immediate response with the use of floral remedies and, in this way, Floral Therapy ofBach finds increasing application in pediatrics, an age group where we find frequentclinical conditions associated with fears and difficulties in adapting. In Brazil this practicewas added to the National Policy for Integrative and Complementary Practices to the SUS inMarch 2018. Several studies have been carried out in several countries on the use of flower remediesin childhood and adolescence to treat fears and traumas, Deficit Disorder Attention and Hyperactivity Disorder, secondary nocturnal enuresis and vitiligo, with results positive as to its effectiveness when compared to the control group. of Bach are shown to be important therapeutic tools for the treatment of disorders infantile emotional disorders reducing the sequels that harmful emotions produce in these children and adolescents, in addition to health promotion, requiring greater dissemination and appreciation in the training of doctors and health professionals in general.
Keywords: Florais de bach; Medicamento; Ambiente e Saúde